Dialoguing with the silent researcher: Rethinking the role of the transcriptionist in qualitative research. Issue 2 (July 2019) - Hurst, Heather; McCallum, Kathryn; Tilles, Sara
Even though transcription is a mainstay of qualitative research, transcription itself is rarely present in discussions of data collection or analysis. A meager body of literature exists that considers transcription as theory, but such literature tends to focus on the transcriptionist's choices. We have few empirical studies on transcription and the role of the transcriptionist. Drawing on frameworks of literacy as a sociocultural process and post-structural feminism, we investigate two cases that demonstrate how the transcriptionist can assume a generative role in research projects. Our data reveal how the transcriptionist shared interpretations, helped make methodological decisions, and was a reader who knew the full body of data. We argue for a reframing of our collective understanding of the transcriptionist and consider the benefits of, limitations to, and ethical issues in involving transcriptionists explicitly as co-researchers.